2021
DOI: 10.21203/rs.3.rs-1054070/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ethnomycological Study of Wild Edible and Medicinal Mushrooms in District Jammu, J&K, India

Abstract: Background: Union Territory of Jammu and Kashmir (J&K) has a rich tradition of usage of wild edible mushrooms (WEM) for culinary and medicinal purposes. But very few studies, restricted to some regions of the Union Territory, have been conducted to enlist the WEM. District Jammu has never been explored for WEM. Moreover, the quantification of the traditional knowledge of WEM has not been carried out as yet in J&K. Therefore, the present study was conducted in Jammu district with aims of; enlisting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Decreased phosphate levels are associated with the development of various disorders such as osteoporosis, osteopenia, rickets, metabolic encephalopathy, and even results in cardiac and pulmonary dysfunction. 47 We observed that secretome treatment resulted in decrease in serum Ca 2+ and increase in PO 4 2− levels in D-gal-treated rats, suggesting that secretome treatment might have lowered the secretion of PTH and hence improved renal reabsorption and excretion of Ca 2+ and PO 4 2− .…”
Section: Dpscs Secretome Contains Antiaging and Neuroprotective Molec...mentioning
confidence: 65%
“…Decreased phosphate levels are associated with the development of various disorders such as osteoporosis, osteopenia, rickets, metabolic encephalopathy, and even results in cardiac and pulmonary dysfunction. 47 We observed that secretome treatment resulted in decrease in serum Ca 2+ and increase in PO 4 2− levels in D-gal-treated rats, suggesting that secretome treatment might have lowered the secretion of PTH and hence improved renal reabsorption and excretion of Ca 2+ and PO 4 2− .…”
Section: Dpscs Secretome Contains Antiaging and Neuroprotective Molec...mentioning
confidence: 65%
“…Hypotension was determined by the admitting diagnosis and recorded blood pressure of less than 90/60 mm Hg. 18 Influence of concomitant antihypertensives was not included in the assessment of hypotension as an AE of gabapentinoids. Serum laboratory chemistries including a complete metabolic panel and blood count were recorded daily when available.…”
Section: Methodsmentioning
confidence: 99%